Difunctionalization of Alkenes Involving Metal Migration - Li, Yuqiang; Wu, Dong; Cheng, Hong‐Gang; Yin, Guoyin (Angewandte Chemie International Edition, 2020)
The direct difunctionalization of alkenes, a cheap and abundant feedstock, represents one of the most attractive strategies for increasing molecular complexity in synthetic organic chemistry. In contrast with the 1,2‐difunctionalization of alkenes, recent advances showcase alkene 1,n‐difunctionalizations (n≠2) involving metal migration is an emerging and rapidly growing area of research. This promising strategy not only opens a novel avenue for future development of alkene transformations, but also significantly expands upon the bond disconnections available in modern organic synthesis. This Minireview summarizes recent progress in the migratory difunctionalization of alkenes, with an emphasis on the driving force for metal migration. Driving force: The difunctionalization of alkenes involving metal migration provides access to a new class of products that are not readily synthesized by other methods. This Minireview summarizes recent advances in the field, with an emphasis on the driving force for metal migration.